First paleoparasitological study of micromammal coprolites from the holocene of the Somuncurá Plateau Protected Natural Area (Patagonia Argentina) - Beltrame, Maria Ornela (2018)
The Somuncurá Plateau is a Protected Natural Area located in the middle of the northern extra-Andean arid Patagonia. Inhabited by at least 20 small mammal species, is the place with the uppermost species richness in Patagonia. The aim of this study was to examine the parasite remains from micromammal coprolites collected in association with a bone sequence recovered at the east of the Somuncurá Plateau (site “Alero Las Lechuzas”). Coprolites came from the four temporal units previously defined: unit I (4790 ± 100 yrs. 14C B.P.), unit II, unit III (7840 ± 120 yrs. 14C B.P.) and unit IV. Each coprolite was processed, rehydrated, homogenized, processed by spontaneous sedimentation and examined using a light microscope. Coprolites and eggs were described, measured and photographed. Samples were positive for two nematode species: Helminthoxys caudatus Freitas, Lent & Almeida, 1937 (Oxyurida, Oxyuridae) and Trichuris spp. (Trichinellida: Trichuridae). This is the first paleoparasitological study developed for the Somuncurá Plateau Protected Area. Moreover, this is the first time that the genus Helminthoxys is reported from ancient times worldwide. Coprolites were attributed to the mountain cavy Microcavia australis (Rodentia, Caviidae).The presence of H. caudatus for the Middle Holocene of northern Patagonia contributes to the study of the history of the histricomorphs and pinworms relationships.